Aging in Europe: Reforms, International Diversification, and Behavioral Reactions - Börsch-Supan, Axel; Härtl, Klaus; Ludwig, Alexander (American Economic Review, 2014)
The extent of demographic changes in Europe is much more drastic than in the United States. This paper studies the effects of population aging on the interactions between economic growth and living standards in Europe with labor market and pension reform, behavioral adaptations, and international capital flows. Our analysis is based on an overlapping generations model with behavioral reactions to reform which is extended to the multi-country situation typical for Europe. While the negative effects of population aging on growth in Europe can in principle be compensated by reforms and economic adaptation mechanisms, they may be partially offset by behavioral reactions.